The Meaning of the Animated Music Video: Luh Ayu Manik Mas from the Perspective of Barthes' Semiology - Devi, Aprilia Trisya; Hutami, Cantika Proborini Sekar; Sompotan, Ronaldo Alexander (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study applies Roland Barthes' semiology theory to analyze semiotics in the animated film Luh Ayu Manik Mas Full Animation New. The film depicts a Balinese heroine striving to safeguard Bali's environment and cultural heritage from various threats. Through semiotic analysis, this research explores the denotative and connotative meanings embedded in the film’s narrative and visual elements, including character representation, traditional Balinese attire, symbols, and rituals. The findings indicate that the stories within each scene highlight Balinese cultural values while promoting environmental conservation. Furthermore, the film reinforces Bali’s indigenous identity by blending modern and traditional elements in its storytelling. The study's results are expected to contribute to media semiotics research, particularly regarding the cultural representation in contemporary animation.